PENGARUH GREEN MARKETING DAN GREEN PRODUCT TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUKIN - Rosyada, Faradilla Amaylia; Dwijayanti, Renny (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine the effect of green marketing and green product partially on the decisions to purchase Sukin product. In addition, this study also aims to determine the effect of green marketing and green product simultaneously on the decision to purchase Sukin product. This research uses descriptive quantitative. The population of this tudy are respondents who have made at least one purchase decision regarding Sukin product. In this study used a purposive sampling technique method of 120 samples. Data was collected via google form and measured with a likert scale using the IBM version 25 of SPSS software with multiple liniear analysis method. The result of this study indicate that there is a partial and simultaneous positive effect on green marketing and green product on purchasing decisions for Sukin product.